ANALISIS PENGARUH PENERIMAAN PAJAK KENDARAAN BERMOTOR DAN BEA BALIK NAMA KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH PROVINSI BANGKA BELITUNG TAHUN 2012-2016 - Novianty Oeiy, Yenny; Medinal; Ahmad Agin, Arka'a (Jurnal Akuntansi Bisnis Dan Keuangan, 2018)
This study aims to determine the effect of Motor Vehicle Tax and Motorcycle Vehicle ownership reverse cost Title to the Local Revenue of Bangka Belitung Islands Province. The result of the research shows that the variable of Motor Vehicle Tax has an effect on the original income of the region, in the form of Motorcycle Vehicle ownership reverse cost, does not affect the local revenue.Based on the results simultaneously using Test F and it is found that the value of Fhitung of 34.230 > Ftabel 19,00, where there is influence between the Motor Vehicle Tax and Motorcycle Vehicle ownership reverse cost to the Local Revenue. In partial result using T Test, the comparison between thitung and ttable for Motor Vehicle Tax shows thitung is bigger than ttable (6,044> 4,30265) means that Motor Vehicle Tax shows significant influence to Local Revenue. Also on result Comparison between thitung and ttable for debt level show thitung is smaller than ttable (0,481 < 4,30265) means Motor vehicle reverse cost reveals insignificant influence to Local Revenue.